Exploring factors influencing health-related quality of life in adult females with injuries: a cross-sectional nationwide study - Kwak, YeunHee; Jang, Insil (Frontiers in Public Health, 2023)
Objectives This study aimed to identify the types of injury experiences affecting adult females and the associations between injury experiences and health-related quality of life. Methods This study used a secondary analysis of cross-sectional data from the Korea National Health and Nutrition Examination Survey, which employed a stratified multistage probability sampling design to obtain nationally representative data. Health-related quality of life was measured with the EuroQol Five-Dimension and consisted of mobility, self-care, usual activity, pain/discomfort, and anxiety/depression. Results Among women aged 19–64, the prevalence of injury experience was 5.9%. Women’s injury experience varied by age, subjective health perception, menstruation details, osteoporosis status, and osteoarthritis status. The following injury experience–related factors were significantly associated with health-related quality of life: self-care (odds ratio [OR] = 0.32, 95% confidence interval [CI]: 0.17–0.60), usual activity (OR = 0.43, 95% CI: 0.27–0.70), and pain/discomfort (OR = 0.56, 95% CI: 0.44–0.72). Conclusion Health-related quality of life among adult women was significantly associated with injury experience. The results of this study highlight risk factors for injury that are associated with aging, such as menopause, osteoporosis, and osteoarthritis. Accurate assessments of pain and discomfort, as well as daily activities, are essential for designing effective interventions for injured women. Tailored training and education can promote self-management and improve outcomes for recovery.